2014
DOI: 10.1038/srep06389
|View full text |Cite|
|
Sign up to set email alerts
|

Micromonospora from nitrogen fixing nodules of alfalfa (Medicago sativa L.). A new promising Plant Probiotic Bacteria.

Abstract: Biotic interactions can improve agricultural productivity without costly and environmentally challenging inputs. Micromonospora strains have recently been reported as natural endophytes of legume nodules but their significance for plant development and productivity has not yet been established. The aim of this study was to determine the diversity and function of Micromonospora isolated from Medicago sativa root nodules. Micromonospora-like strains from field alfalfa nodules were characterized by BOX-PCR finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 59 publications
1
43
0
1
Order By: Relevance
“…However, their presence was sporadic, meaning that they are found in only a few of the investigated samples. Even though many strains of Enterobacteriaceae possess plant growth promoting traits, such as production of indole acetic acid (Aserse et al, 2013), and, as shown for other bacterial groups (Martínez-Hidalgo et al, 2014), might actually promote plant growth, the role of these NRE still needs to be investigated. It is possible that depending on environmental conditions effects on plant fitness might vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their presence was sporadic, meaning that they are found in only a few of the investigated samples. Even though many strains of Enterobacteriaceae possess plant growth promoting traits, such as production of indole acetic acid (Aserse et al, 2013), and, as shown for other bacterial groups (Martínez-Hidalgo et al, 2014), might actually promote plant growth, the role of these NRE still needs to be investigated. It is possible that depending on environmental conditions effects on plant fitness might vary.…”
Section: Discussionmentioning
confidence: 99%
“…Even though those strains do not induce nodule formation, they might be able to enter infection threads when co-inoculated with rhizobial strains (Pandya et al, 2013; Zgadzaj et al, 2015). NRE include potential plant growth promoting rhizobacteria (PGPR), as some of the investigated strains display PGPR traits, such as indole acetic acid production or phosphate solubilization (Li et al, 2012), or enhance nodulation when co-inoculated with a rhizobial symbiont compatible with the host plant (Martínez-Hidalgo et al, 2014). Nevertheless, the role of NRE present in the nodules remains mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen fixation is one of the most important of all PGPB traits, and several methodologies have been employed to measure the nitrogen-fixing capabilities of a strain (e.g., Wertz et al 2012). However, the ability to grow in an N-limited environment is not a test for nitrogen-fixation ability because the media used are rarely completely depleted of nitrogen, which leads to false positives (Martínez-Hidalgo et al 2014a). For example, bacteria that either effectively scavenge N or have 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity may survive for a time on an N-free medium Fig.…”
Section: Traits For Promoting Plant Growthmentioning
confidence: 99%
“…Although Micromonospora strains are not associated with biological nitrogen fixation (Martínez-Hidalgo et al 2014b), they are common inhabitants of both legume and actinorhizal nodules, and frequently in high numbers (Trujillo et al 2015). In addition, Micromonospora strains are important agents for biocontrol and plant growth promotion (Martínez-Hidalgo et al 2014a, 2015. Like the Firmicutes, Actinobacteria have been co-inoculated with nitrogen-fixing rhizobia onto legumes to enhance the mutualistic interaction (Solans et al 2009;Benito et al 2017).…”
Section: Biosafety Tests For Bioinoculantsmentioning
confidence: 99%
“…This is largely due to their ability to produce secondary metabolites that have antibiotic properties (Supong et al , 2013). Additionally, several strains have been proposed as potential candidates for plant growth-promoting bacteria through nitrogen fixation and antagonistic activities against phytopathogens (Martínez-Hidalgo et al , 2014; Raaijmakers & Mazzola, 2012). The typical characteristic of members in this genus is the formation of single, non-motile spores on sporophores of the substrate mycelium and the absence of aerial mycelium (Nimaichand et al , 2013; Ren et al , 2013).…”
mentioning
confidence: 99%